Study of Important Blood Metabolites of Surti Goats under Different Estrus Synchronization Protocols - Yede, Amol B.; Khasatiya, Chandubhai T.; Singh, Virendra Kumar; Londhe, Arvind S.; Urkude, Atul (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
Reproduction is the key to livestock production especially in goats that have high reproduction potential. Estrus synchronization is useful  for rhythmic coordinated variation in reproductive hormones along with level of serum metabolites. Present study was conducted to  evaluate variations of important blood biochemical metabolites in Surti goats under different estrus synchronization protocols. 18 Surti  goats were divided equally (n=6) in 3 groups, viz., G1, G2 and G3 (control). G1 and G2 groups were injected i/m with GnRH analogue,  Buserelin acetate 4.2 μg, on day 0 and 11 and PGF2α analogue, Dinoprost tromethamine 10 mg, on day 9. Progestogen sponge was  also kept intravaginal in G1 group on day 0 and removed on day 11 before Buserelin injection. G3 group acted as control and received  placebo of 2 ml normal saline simultaneous to treatment groups. Blood was collected on day 0, 5th, 11th, on the day of estrus and on  day 30th post-estrus/mating for analysis of serum glucose, total protein and cholesterol. Levels of glucose, total protein and cholesterol  varied non-significantly between groups, but within the group total cholesterol levels increased significantly (p
Keywords: Estrus synchronization; Goat; Ovsynch (GPG); Intravaginal progestagen; Serum